Efektivitas Penggunaan Kartu Kata Bergambar Pada Anak Disleksia Kelas IV SD - Nurika Lestari; Mega Iswari; Arisul Mahdi (Jurnal Penelitian Pendidikan Khusus, 2022)
This study reveals the child’s ability to read words that contain nouns and proves the efectiveness of picture word card media improving reading skills in children. Where the researchers found this problem in the fourth grade of elementary school when carrying out field observations. From theobservations, it was found that children had difficulty in reading words. Researchers are interested in teaching children to learn to read words through picture word cards. This research metod uses a singel subject research (SSR) with the subject, namely TS, who is in the fourth grade of SD N 011 Titian Resak. Data on children’s ability to read words were obtained through observation and test. The design used is A-B-A to see the level of children”s ability to rerad words before being given the intervention (A1), the condition (B), and after being given the intervention (A2). The results of the study stated that the child’s ability in each condition was to get a score of 0%, in condition A1, when given intervention the child gets a score of 40 % while in condition A2 the child gets a score of 100%. With the ability mastered, each condition increases. It can be seen that the results of data analysis showed that the intervention treatment with picture word cards are efective for improving word reading skills in dyslexic children. It is proven by an increase in the ability to read words from the basline condition to the condition after being given intervention using picture wod cars media.